Democracia e gestão da educação: uma abordagem do poder na escola - Markowicz, Daniel (2010)
The object of this work is to research about the power of education management in a public school located in the metropolitan area of Curitiba. The investigation is conceived by speech analysis, power relations, and institution’s documents. Intend to examine the speeches that cross themselves in all the segments of public school’s management in the scholarship quotidian and your own logic to think how the mechanisms and the effects of the power of management in the public school work. The study is presenting in the foucaultiana perspective. Study the power relations of democratic education management. The research problem refers of how to comprehend the mechanisms of management education’s power functioning, in special basic education of public education. Some publics politics returned to the education are analysis in here as speeches and documents that show the power’s dislocating and your insidious action, in the way that to point new perspectives for the education and, or, the least, the needy to accept or realize changes in direction to emancipation. The education management is returned as a stage to the discussion that comprises the power relations and the social relations in fight and resistance in the educational work, as a debate’s space. In the field’s study, the analysis developed by means of bibliographic investigation and documental about the education democratic management, in the study the municipal plan of education and the study the case of Anita Canet’s school. In synthesis, it’s an approaching about the speech and the power in Foucault analyzing documents about education with emphasis in the study of Political Pedagogic Project and the Scholarship Guide Rule. So, the work reveal in the school there is a crossing speeches affecting the practical, over all denominates the democratic management.